2021
DOI: 10.5435/jaaos-d-20-01322
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Simulation for Interactive Visualization of 3D Fracture Fixation Biomechanics

Abstract: Introduction: In the surgical fixation of fractures, proper biomechanical stability is key in preventing clinical complications including poor fracture healing, residual deformity, loss of fixation, or implant failure. Stability is largely influenced by treatment decisions made by the surgeon. The interplay of surgeon-controlled variables and their effect on the three-dimensional (3D) biomechanics of a fracture fixation construct are often not intuitive, and current training methods do not facilitate a deep un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[3][4][5][6]11,34 These simplified generic models are suitable for investigation and demonstration of fundamental principles. 35 We caution against direct extrapolation of results here to specific clinical settings. Although we believe the findings of this investigation would generalize well to many specific bone geometries (e.g., curvature and cortical thickness), bone properties, and fracture types/geometries, further work is warranted in this area.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[3][4][5][6]11,34 These simplified generic models are suitable for investigation and demonstration of fundamental principles. 35 We caution against direct extrapolation of results here to specific clinical settings. Although we believe the findings of this investigation would generalize well to many specific bone geometries (e.g., curvature and cortical thickness), bone properties, and fracture types/geometries, further work is warranted in this area.…”
Section: Discussionmentioning
confidence: 93%
“…Transverse planar fractures were modeled for simplicity, as was the case for most previous experimental studies of dynamic compression plates 3–6,11,34 . These simplified generic models are suitable for investigation and demonstration of fundamental principles 35 . We caution against direct extrapolation of results here to specific clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated improvements in biomechanical knowledge after a session with FractSim. 25 The aim of this study was to add visualization of the effects of fracture healing to FractSim (Fig. 3 ).…”
Section: Fractsim Software For Visualization Of 3d Fracture Fixation ...mentioning
confidence: 99%